MAPEAMENTO DE LOCOS DE RESISTÊNCIA QUANTITATIVA À ANTRACNOSE FOLIAR EM MILHO TROPICAL - Romanek, Cristiane (2014)
The objectives of this study were to characterize the resistance/susceptibility of the F2:3 maize progenies to anthracnose leaf blight (Colletotrichum graminicola), to estimate the genetic parameters associated with resistance, and map the genomic regions associated with quantitative resistance loci (QRL) by means molecular markers microsatellites (SSRs) and AFLPs. The inbred lines L04-2 (resistant) and L95-1 (susceptible) were crossed to generate an F2 population. Individuals of this population were selfed resulting F2:3 progenies, these were evaluated in three trials conducted in a randomized block design, with three replications. The treatments were consisted of 121 F2:3 progenies, parental lines and F1 generation. Plants were inoculated in two times between the stages V6 and V7, the second inoculation made seven days after the first. Three evaluation of the severity of anthracnose leaf blight were conducted: the 1st in VT (flowering) stage, 2nd in R2 and 3rd in R3 through a note scale with amplitude from 1 to 6. From the point assessments, was calculated the area under the disease progress curve (AUDPC). The results showed highly significant effects for both point assessments for AUDPC, indicating high genetic variability for resistance to anthracnose leaf blight among the F2:3 progenies. The high magnitude of genetic parameters indicate that the genetic control of resistance to anthracnose leaf blight of corn is associated with the expression of genes of great phenotypic effect. QRL mapping was conducted based on phenotypic analysis of 121 F2:3 progenies, evaluated in three experiments for three point assessments and AUDPC. Linkage analysis between the markers (microsatellites and AFPLs) and QRLs was performed by analysis of multiple linear regression and by composite interval mapping. Multiple linear regression identified mark SSRs and AFPLs highly associated with resistance alleles, the E55139 and E56386 AFLPs loci with the highest partial regression coefficients for the three experiments, with amplitudes from 6,67 to 31,31 % and 6,12 to 21,78 %, respectively. Were mapped 19 QRLs to anthracnose leaf blight in eight linkage groups. Six QRLs were the most stable environments for different evaluation and responsible for the large magnitude of the phenotypic variation in resistance. The high number of QRLs mapped in this population confirms the pattern of quantitative inheritance of resistance in tropical maize to anthracnose leaf blight caused by C. graminicola.